A new species of Moneuptychia Forster (Lepidoptera: Satyrinae: Euptychiina) from central Brazil - Freitas,André V L (2010)
This paper describes a new species of Moneuptychia Forster from the cerrado in the Federal District and Goiás region in central Brazil, and from highland open vegetation (campos de altitude) of Minas Gerais and Paraná. We provide details of the adult morphology and discuss the new species placement in the genus Moneuptychia.